Respuesta :

Answer:

(7, 1 )

Step-by-step explanation:

2x + 5y = 19 → (1)

3x - 2y = 19 → (2)

multiplying (1) by 2 and (2) by 5 then adding will eliminate y

4x + 10y = 38 → (3)

15x - 10y = 95 → (4)

add (3) and (4) term by term to eliminate y

19x + 0 = 133

19x = 133 ( divide both sides by 19 )

x = 7

substitute x = 7 into either of the 2 equations and solve for y

substituting into (1)

2(7) + 5y = 19

14 + 5y = 19 ( subtract 14 from both sides )

5y = 5 ( divide both sides by 5 )

y = 1

solution is (7, 1 )